COG6‐CDG: Expanding the phenotype with emphasis on glycosylation defects involved in the causation of male disorders of sex development. Issue 4 (4th August 2020) - Mandel, Hanna; Cohen Kfir, Nehama; Fedida, Ayalla; Shuster Biton, Efrat; Odeh, Marwan; Kalfon, Limor; Ben‐Harouch, Shani; Fleischer Sheffer, Vered; Hoffman, Yoav; Goldberg, Yael; Dinwiddie, April; Dumin, Elena; et al.
Abstract: COG6‐congenital disorder of glycosylation (COG6‐CDG) is caused by biallelic mutations in COG 6. To‐date, 12 variants causing COG6‐CDG in less than 20 patients have been reported. Using whole exome sequencing we identified two siblings with a novel homozygous deletion of 26 bp in COG6, creating a splicing variant (c.518_540 + 3del) and a shift in the reading frame. The phenotype of COG6‐CDG includes growth and developmental retardation, microcephaly, liver and gastrointestinal disease, hypohydrosis and recurrent infections. We report two patients with novel phenotypic features including bowel malrotation and ambiguous genitalia, directing attention to the role of glycoprotein metabolism in the causation of disorders of sex development (DSD). Searching the glycomic literature, we identified 14 CDGs including males with DSD, a feature not previously accentuated. This study broadens the genetic and phenotypic spectrum of COG6‐CDG and calls for increasing awareness to the central role of glycosylation processes in development of human sex and genitalia. Abstract :